Indigenous Perspectives: the Post-Conflict Landscapes of Rwanda - Killian Doherty (Footprint)
Much of Rwanda’s conflict can be traced to the relation between human (culture) and non-human (nature) that defined territories and ethnic divisions in pre-colonial Rwanda. These human and non-human relations, exploited by European colonialism, have become increasingly estranged through the influence of Eurocentric forms of architecture, urban and rural planning. This practice-based research explores the relations between Rwanda’s human settlements and the landscape to provide insight into emergent spaces of conflict. The hope is that where a meeting of different perspectives is articulated a form of architecture as mediation may emerge.